Self-Regulated Learning (SRL) untuk Meningkatkan Disiplin Mahasiswa - Roiyan One Febriani; Dedy Reza Sukmana; Vannisa Aviana Melinda; Dian Eka Aprilia Fitria Ningrum; Imroatul Hayyu Erfantinni; Sufeeyah Maseng (Pamomong: Journal of Islamic Educational Counseling, 2024)
Discipline is a form of obedience and compliance by an individual to the values and norms prevalent in the community. This study aims to determine the effectiveness of self-regulated learning (SRL) in enhancing Muslim students' discipline. This research adopts a quantitative approach with a pretest-posttest control group design. Twelve Muslim students were selected as research subjects using purposive sampling techniques. The experimental group comprised six individuals, while the control group comprised six. Data analysis was conducted using the Wilcoxon test. The results of the Wilcoxon test showed p= .027; p<.05 for the experimental group and p= .026; p<.05  for the control group. Based on the hypothesis test, it was proven that H0 is rejected. This indicates that the SRL technique is equally effective than the reality approach, although the average discipline improved more than other interventions. The findings of this study suggest that Self-Regulated Learning is one of the techniques that can be employed to enhance the discipline of Muslim students.